Self-Efficacy: Readiness of Teachers in Inclusive Schools - Wahyuni, Sri; Novembli, Meta Silfia; Hasanah, Nisaul (AL-ISHLAH: Jurnal Pendidikan, 2024)
Inclusive education involves ensuring that all students, including those with disabilities, have access to and participate fully in their educational environment as a fundamental right. Central to this is the concept of teacher self-efficacy, which refers to a teacher's belief in their ability to effectively instruct diverse learners. Teachers with high self-efficacy are more likely to approach disabilities with a positive and inclusive mindset, whereas those with lower self-efficacy often demonstrate less inclusive attitudes. This study aimed to assess whether teachers in inclusive primary schools possess the self-efficacy needed to effectively teach students with disabilities. A descriptive and quantitative methodology was employed, involving all 40 teachers within the study. Findings revealed that teachers in inclusive elementary schools tend to exhibit lower self-efficacy when addressing disabilities outside their area of expertise. Across various self-efficacy dimensions—such as inclusive teaching, collaboration, and behavior management—teachers were generally rated as moderate, regardless of the extent of direct interaction with students with disabilities. The results indicate a need for targeted professional development and training to enhance teachers' ability to support students with disabilities more effectively.